Equipment's role on the drying process of chestnut (Castanea sativa Mill.) fruits - Lamas, Hugo (2017)
In the present work, drying of chestnut (Castanea sativa Mill.) fruits was performed at different air temperatures in three equipments - convection oven, parallel flow tray dryer and fluidised bed dryer, at temperatures between 40 and 100°C. Newton diffusion approach and two-term models were found to be adequate in describing the moisture ratio and drying rates along time. For the same temperature, the dehydration processes that involved higher air velocities were > 1.6 times faster. On the other hand, for the same equipment the highest temperature (100°C) induced a drying rate ten times faster than the lowest temperature (40°C), reducing drying time. Apparent diffusivity ranged between 7.03 × 10^-11 m2 s-1 (40°C, convection oven) and 1.06 × 10^-9 m2 s-1 (100°C, fluidised bed dryer). In convection oven experiments, the diffusivity in function of temperature was well described by an Arrhenius type function, with an activation energy of 4.08 × 10^4 J mol-1.